Wireless Gesture Controlled Semi-Humanoid Robot - Toshika Fegade; Yogesh Kurle; Sagar Nikale; Praful Kalpund (Institute of Advanced Engineering and Science, 2016)
Robotics is a field concerned with the “intelligent connection of perception of action”. The most common manufacturing robot is the robotic arm with different degree of freedoms. Today, these humanoids perform many functions to assist humans in different undertakings such as space missions, driving and monitoring high speed vehicles. They are called semi-humanoids because they resemble to upper part of human body. The idea of this paper is to change perception of controlling robotic arm. This paper provides a way to get rid of old fashioned remote controls and gives an intuitive technique for implementation of Semi-Humanoid Gesture controlled robot. It includes two robot arms which are exactly similar to human arm (5 fingers) increasing sensitivity of the system. It includes motion sensors -flex and accelerometer (used in mobile phones for tilting motion). The system design is divided into 3 parts namely: Robotic Arm, Real time video and Platform. The prime aim of the design is that the robot arm and platform starts the movement as soon as the operator makes hand and leg gesture. The Robotic arm is synchronized with the gestures (hand postures) of the operator and the platform part is controlled by the leg gestures of the operator. The robot and the Gesture device are connected wireless via RF. The wireless communication enables user to interact with the robot in an effortless way.